Topographic and Climatic Control on Chemical Weathering of Mountainous Riverine Sediments of Hainan Island, South China Sea - Xu, Fangjian; Hu, Bangqi; Zhao, Jingtao; Liu, Xiting; Cui, Ruyong; Ding, Xue; Wang, Guifeng; Huang, Jianping (Frontiers in Earth Science, 2022)
Hainan Island, the largest island in the northwestern South China Sea (SCS), is characterized by many tropical mountainous rivers that flow into the SCS. The geochemistry of these riverine sediments and the factors controlling the weathering intensity is still not well understood. In this study, sedimentary geochemistry has been investigated by using 45 riverine sediments collected from 18 major rivers on Hainan Island. The Hainan sediments are only first-cycle rather than polycyclic sediments, they faithfully reflect the present weathering intensity. The high and steady values of Chemical Index of Alteration (CIA) indicate that the riverine sediments at different parts of the Hainan Island have been overall undergone intensive chemical weathering. The low values of Weathering Index of Parker (WIP), high , , , and values of north Hainan indicate the highest weathering degree, which is mainly influenced by the flat topography. The higher values of , , , and of southwest Hainan than those of east Hainan suggest that the leaching of elements such as Na, K, Sr, and Ba is more extreme (i.e., more intensive weathering). These are mainly caused by the different physical denudation due to different summer precipitation. Overall, the Hainan Island is featured by intensive chemical weathering and is classified as a typical transport-limited weathering regime. Therefore, the geochemistry of the riverine sediments of Hainan Island is different from those of sediments in tectonically active regions (e.g., Taiwan Island).